2011
DOI: 10.1007/s12639-011-0057-0
|View full text |Cite
|
Sign up to set email alerts
|

A survey on endoparasites and ectoparasites of stray cats from Mashhad (Iran) and association with risk factors

Abstract: As there appeared to be no data available on parasite infection of stray cats in the region and considering the potential threat of stray cats for animal and public health, the present study was carried out using biological samples and necropsy finding collected from cats captured in Mashhad city in the northeast of Iran. From a total 52 stray cats examined, 18 (34.6%) were male and 34 (65.4%) were female. Ten species of endoparasites including helminthes and protozoa and two species of ectoparasites were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
6
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 31 publications
6
23
6
2
Order By: Relevance
“…Coman attribute the prevalence of this cestode with the importance of rodent in the diet of these cats (Coman 1972). In our study, the prevalence of the D. caninum was 58 %, which is compatible with the findings of the previous studies done in Brazil (52.6) (Labarthe et al 2004) and Iran (68.1 and 49.5 %) (Arbabi and Hooshyar 2009;Zibaei et al 2007), However, the prevalence of this parasite was higher than the previously recorded rates by other surveys from various countries (Borji et al 2011;Calvete et al 1998;Canto et al 2013;Dalimi and Mobedi 1992;Jittapalapong et al 2007;Khalafalla 2011;Lefkaditis et al 2014;Raji et al 2013;Ramos et al 2013). High prevalence of this parasite in resent survey could be due to the fact that D. caninum requires fleas as intermediary hosts and cats infected after ingesting infected fleas (Labarthe et al 2004).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Coman attribute the prevalence of this cestode with the importance of rodent in the diet of these cats (Coman 1972). In our study, the prevalence of the D. caninum was 58 %, which is compatible with the findings of the previous studies done in Brazil (52.6) (Labarthe et al 2004) and Iran (68.1 and 49.5 %) (Arbabi and Hooshyar 2009;Zibaei et al 2007), However, the prevalence of this parasite was higher than the previously recorded rates by other surveys from various countries (Borji et al 2011;Calvete et al 1998;Canto et al 2013;Dalimi and Mobedi 1992;Jittapalapong et al 2007;Khalafalla 2011;Lefkaditis et al 2014;Raji et al 2013;Ramos et al 2013). High prevalence of this parasite in resent survey could be due to the fact that D. caninum requires fleas as intermediary hosts and cats infected after ingesting infected fleas (Labarthe et al 2004).…”
Section: Discussionsupporting
confidence: 92%
“…High prevalence of this parasite in resent survey could be due to the fact that D. caninum requires fleas as intermediary hosts and cats infected after ingesting infected fleas (Labarthe et al 2004). T. hydatigera prevalence of 24 % found in the current study was higher than that reported by Borji et al (2011) Furthermore, compared with some previous studies, such as; 5 % in Egypt (Khalafalla 2011), 7.69 and12.9 % in Iran (Borji et al 2011;Zibaei et al 2007), 11.9 % in Brazil (Labarthe et al 2004), 1 % in Mexico (Canto et al 2013), 3.33 % in Nigeria (Raji et al 2013), the prevalence of T. leonine was higher (30 %). But Lefkaditis et al (2014) detected a rate of 93 % in Greece (Lefkaditis et al 2014).…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations